Repair of Taussig-Bing anomaly with unusual coronary pattern using autologous pericardial tube extension - AshishKatewa; FitoonYaldo; AtulPrabhu; BalajiSrimurugan (Wolters Kluwer Medknow Publications, 2021)
The incidence of unusual coronary patterns including single coronary artery is high in Taussig-Bing anomaly (TBA). The relocation of a single coronary artery from a nonfacing sinus can be technically challenging with implications on early and late outcomes. Many innovative techniques for coronary transfer have been described and no coronary pattern precludes arterial switch operation in the current era. We describe a technique of coronary transfer using autologous pericardial tube extension with good early outcome.